Technological assimilation and divergence in times of crisis - Álvarez, Isabel; Di Caprio, Debora; Santos-Arteaga, Francisco Javier (Technological and Economic Development of Economy, 2016)
We study an endogenous stochastic growth model whose dynamic evolution is determined by an adaptive learning process defining the accumulation of technological knowledge within countries. Both the assimilation of technological knowledge and the arrival rate of innovations depend on the technological development level of countries. We illustrate how heterogeneous levels of technological development provide laggard countries with insufficient innovation incentives, leading to divergences in total factor productivity and their technological stagnation. The model is simulated numerically using data from the current Innovation Union Scoreboard where the main expected growth patterns of the Baltic States are compared to those of the reference innovators within the European Union area. First published online: 10 Jun 2015